Universal newborn hearing screening: the experience of the University Hospital of Parma - Magnani, Cinzia; Bacchi, Giovanna; Borghini, Anna Maria; Delmonte, Daniela; Fava, Giovanni; Occasio, Anna Maria; Sarti, Annarita; Vincenti, Vincenzo (Acta Biomedica Atenei Parmensis, 2015)
Abstract Background and aim: Early diagnosis of congenital deafness is fundamental to minimize the negative consequences on a child’s educational and psychosocial development. To lower the age of hearing-impaired children at the time of diagnosis, universal neonatal hearing screening (UNHS) is considered essential. The aim of this study was to review tha data of the first 4 years of implementation of UNHS in the University Hospital of Parma. Methods: 11624 infants born between February 2010 and December 2013 were included into the study. Transient evoked otoacoustic emissions were used as screening test. When the newborn had failed at the initial test, he was re-tested within 3 weeks from birth. If the same result was obtained at the second step, the newborns were referred for clinical auditory brainstem response. We calculated quality indicators and compared them with international guidelines. Results: 11592 infants (99.7%) were screened during the birth admission. 10359 (88.5%) were well-babies, while 1233 (11.5%) had audiological risk factors. Among 11592 newborns screened, 42 (3.59‰) had a final diagnosis of sensorineural hearing loss. The incidence of deafness was 1.64‰ in well-babies, and 2.02% in neonates with audiological risk factors. Only 71 infants (0.6%) did not complete the screening program. False-positive rate was 1.7%. Conclusions: The analysis of benchmarks and outcomes of UNHS demonstrated the good quality of our hearing screening program. Introduction of automated auditory brainstem response as well as enhanced enrollment of patients who do not complete the screening could further improve the quality program.